2014
DOI: 10.3161/150811014x687369
|View full text |Cite
|
Sign up to set email alerts
|

A Recent Bat Survey Reveals Bukit Barisan Selatan Landscape as a Chiropteran Diversity Hotspot in Sumatra

Abstract: National Park is one of the last refuges protecting intact forest and a representative mammalian fauna in Sumatra. However, knowledge of bat diversity in the area is limited. From 2010 to 2012, 47 bat species were recorded through a series of surveys in 12 localities within and around the national park. An additional six species from the area were identified from the mammal collection of the Museum Zoologicum Bogoriense, Indonesia. At least seven of the species reported in this study are new records for Sumatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 508 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…We confirmed the unidentified Glischropus bat reported by Huang et al (2014) as a species distinct from its congeners, representing a new species of the genus. Previously, only G. tylopus has been confirmed from Sumatra with records known exclusively from the province of North Sumatra (van Strien 1996; Csorba 2011; Csorba unpublished data); hence, according to our present knowledge, the two species are allopatric on the island.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…We confirmed the unidentified Glischropus bat reported by Huang et al (2014) as a species distinct from its congeners, representing a new species of the genus. Previously, only G. tylopus has been confirmed from Sumatra with records known exclusively from the province of North Sumatra (van Strien 1996; Csorba 2011; Csorba unpublished data); hence, according to our present knowledge, the two species are allopatric on the island.…”
Section: Discussionsupporting
confidence: 73%
“…The subsequent investigation of the holotype and three topotype specimens of G. batjanus stored in the collection of Museum für Naturkunde, Berlin supported this view (Csorba unpublished data); hence, currently three species are recognized in the genus: G. tylopus, G. javanus, and the recently described G. bucephalus (Csorba 2011). During review of material recently collected in Sumatra, Indonesia, Huang et al (2014) reported one specimen of a yet undescribed species that belongs to the Glischropus genus. In this paper we describe this new species using morphological and molecular evidence.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Bats are generally common and diverse in coffee‐dominated landscapes across tropical regions (the Neotropics—reviewed by Maas et al., , the Asian tropics—Huang et al., ; Wordley et al., ). However, the abundance and species richness of bats in coffee farms decreases as management intensifies (Mendenhall et al., ).…”
Section: Introductionmentioning
confidence: 99%